Distribution of indium in the Animas - Chocaya - Siete Suyos District - Martinez, Malena Cazorla (2019)
The Ánimas-Chocaya-Siete Suyos district in SW Bolivia hosts a Bolivian-type polymetallic vein mineralization composed mostly of cassiterite, sphalerite, pyrite, galena, stannite, lead sulfosalts, tin sulfosalts and silver sulfosalts. In addition to base (Zn, Sn, Pb) and precious (Ag) metals, important concentrations of In have been described. Systematic EPMA analyses have revealed that the highest concentrations are found in an early generation of sphalerite (up to 9.66 wt% In) and in stannite (up to 4.11 wt% In). Although In-bearing sphalerites are relatively Fe-rich (mostly between 6.0 and 18.1 mol % FeS), the atomic concentrations of these two elements do not yield any correlation. In contrast, In is positively correlated with Cu mostly along a Cu/In = 1 proportion pointing to a (In 3+ + Cu +) -> 2Zn 2+ coupled substitution. A relatively high activity of Cu during the crystallization of In-rich sphalerite is also supported by exsolutions of chalcopyrite and stannite.